In silico study about β-amyloid’s role in Alzheimer’s disease and glaucoma and prediction of its interactions with glaucoma related proteins - Nancy Maurya (Exploration of Drug Science)
Aim: The significance of β-amyloid protein as a key player in neuro-degenerative disorders viz. Alzheimer’s disease (AD), Parkinson’s disease (PD) has been extensively researched and reported. Glaucoma being another prominent form of neuro-degeneration involving the loss of retinal ganglion cells (RGCs) and human trabecular meshwork (HTM) cells, is also found to be similar to AD in many aspects, but its relation with β-amyloid has not been studied too far up to understanding its causation and pathogenesis where β-amyloid is expected to play important role. This study is an attempt to evaluate the chances of β-amyloid’s role in pathogenesis of retinal neurodegenerative disorder called glaucoma, in silico. Methods: The study involved determination of feasibility of interaction between β-amyloid and well known glaucoma related proteins namely, myocilin and optineurin. The computational tool called Hex 8.0.0 has been used in this work. Results: The docking score for β-amyloid and myocilin was found to be –724.1 kJ mol–1 while that for β-amyloid and wild-type optineurin pair was found to be –296.9 kJ mol–1 and that for β-amyloid and mutated optineurin was –607.1 kJ mol–1. Conclusions: Interaction of β-amyloid with myocilin and optineurin in both forms (wild-type and mutated) is quite energetically favorable. The binding between β-amyloid and mutated optineurin is higher in comparison to that between β-amyloid and wild-type optineurin. Thus, functional significance of β-amyloid in glaucoma pathogenesis is fairly possible which should be studied and proved through in vitro and in vivo studies.